Characterization of Simultaneous Pressure Waves as Biomarkers for Colonic Motility Assessed by High-Resolution Colonic Manometry - Chen, Ji-Hong; Parsons, Sean P.; Shokrollahi, Mitra; Wan, Andrew; Vincent, Alexander D.; Yuan, Yuhong; Pervez, Maham; Chen, Wu Lan; Xue, Mai; Zhang, Kailai K.; Eshtiaghi, Arshia; Armstrong, David; et al. (Frontiers in Physiology, 2018)
Simultaneous pressure waves (SPWs) in manometry recordings of the human colon have been associated with gas expulsion. Our hypothesis was that the SPW might be a critical component of most colonic motor functions, and hence might act as a biomarker for healthy colon motility. To that end, we performed high-resolution colonic manometry (HRCM), for the first time using an 84-sensor (1 cm spaced) water-perfused catheter, in 17 healthy volunteers. Intraluminal pressure patterns were recorded during baseline, proximal and rectal balloon distention, after a meal and following proximal and rectal luminal bisacodyl administration. Quantification was performed using software, based on Image J, developed during this study. Gas expulsion was always associated with SPWs, furthermore, SPWs were associated with water or balloon expulsion. SPWs were prominently emerging at the termination of proximal high amplitude propagating pressure waves (HAPWs); we termed this motor pattern HAPW-SPWs; hence, SPWs were often not a pan-colonic event. SPWs and HAPW-SPWs were observed at baseline with SPW amplitudes of 12.0 ± 8.5 mmHg and 20.2 ± 7.2 mmHg respectively. The SPW occurrence and amplitude significantly increased in response to meal, balloon distention and luminal bisacodyl, associated with 50.3% anal sphincter relaxation at baseline, which significantly increased to 59.0% after a meal, and 69.1% after bisacodyl. Often, full relaxation was achieved. The SPWs associated with gas expulsion had a significantly higher amplitude compared to SPWs without gas expulsion. SPWs could be seen to consist of clusters of high frequency pressure waves, likely associated with a cluster of fast propagating contractions. SPWs were occasionally observed in a highly rhythmic pattern at 1.8 ± 1.2 cycles/min. Unlike HAPWs, the SPWs did not obliterate haustral boundaries thereby explaining how gas can be expelled while solid content can remain restrained by the haustral boundaries. In conclusion, the SPW may become a biomarker for normal gas transit, the gastrocolonic reflex and extrinsic neural reflexes. The SPW assessment reveals coordination of activities in the colon, rectum and anal sphincters. SPWs may become of diagnostic value in patients with colonic dysmotility.